2005
DOI: 10.1111/j.1365-2958.2005.04949.x
|View full text |Cite
|
Sign up to set email alerts
|

A small RNA inhibits translation of the histone‐like protein Hc1 in Chlamydia trachomatis

Abstract: SummaryThe chromatin of chlamydial elementary bodies (EBs) is stabilized by proteins with sequence homology to eukaryotic H1. These histone homologues, termed Hc1 and Hc2, are expressed only during the late stages of the chlamydial life cycle concomitant with the reorganization of reticulate bodies (RBs) into metabolically inactive EBs. Hc1 and Hc2 play a major role in establishment of nucleoid structure as well as in downregulation of gene expression as RBs differentiate back to EBs. The effects of Hc1 on gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 32 publications
1
90
0
Order By: Relevance
“…The resulting lncRNA products might simply represent byproducts of transcription and are typically rapidly degraded after synthesis (Clark et al, 2012). (Albrecht et al, 2010(Albrecht et al, , 2011Chabelskaya et al, 2014;Chao et al, 2012;Gong et al, 2011;Grieshaber et al, 2006;Mann et al, 2012;Moon et al, 2013;Ortega et al, 2012;PadalonBrauch et al, 2008;Pfeiffer et al, 2007) crRNA, (Bhaya et al, 2011;Heidrich and Vogel, 2013;Sampson et al, 2013;van der Oost et al, 2014) (Georg and Hess, 2011;Giangrossi et al, 2010;GonzaloAsensio et al, 2013;Gottesman and Storz, 2011;Lasa et al, 2011;Lee and Groisman, 2010;Padalon-Brauch et al, 2008;Sesto et al, 2013) circRNAs rare varies arise from the 3'-5' ligation of both ends of linear RNA molecules n. a. -- (Doose et al, 2013;Vicens and Cech, 2009) - (Conway et al, 2014;Weinberg et al, 2009) Carpenter et al, 2013;Gomez et al, 2013;Iiott et al, 2014;Imamura et al, 2014;Li et al, 2014;Rapicavoli et al, 2013) poly ( …”
Section: Eukaryotic Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%
“…The resulting lncRNA products might simply represent byproducts of transcription and are typically rapidly degraded after synthesis (Clark et al, 2012). (Albrecht et al, 2010(Albrecht et al, , 2011Chabelskaya et al, 2014;Chao et al, 2012;Gong et al, 2011;Grieshaber et al, 2006;Mann et al, 2012;Moon et al, 2013;Ortega et al, 2012;PadalonBrauch et al, 2008;Pfeiffer et al, 2007) crRNA, (Bhaya et al, 2011;Heidrich and Vogel, 2013;Sampson et al, 2013;van der Oost et al, 2014) (Georg and Hess, 2011;Giangrossi et al, 2010;GonzaloAsensio et al, 2013;Gottesman and Storz, 2011;Lasa et al, 2011;Lee and Groisman, 2010;Padalon-Brauch et al, 2008;Sesto et al, 2013) circRNAs rare varies arise from the 3'-5' ligation of both ends of linear RNA molecules n. a. -- (Doose et al, 2013;Vicens and Cech, 2009) - (Conway et al, 2014;Weinberg et al, 2009) Carpenter et al, 2013;Gomez et al, 2013;Iiott et al, 2014;Imamura et al, 2014;Li et al, 2014;Rapicavoli et al, 2013) poly ( …”
Section: Eukaryotic Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%
“…Recently a small regulatory RNA gene was identified as a suppressor of the lethal phenotype of hctA overexpression in Escherichia coli and it was shown to negatively regulate Hc1 synthesis at an early stage of infection (Grieshaber et al, 2006). These histone-like proteins may act as global transcriptional regulators and play a critical role for the transformation of vegetative RBs into infectious EBs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a small regulatory RNA gene was identified as a suppressor of the lethal phenotype of hctA overexpression in Escherichia coli and it was shown to negatively regulate Hc1 synthesis at an early stage of infection (Grieshaber et al, 2006 HEp-2 cells (ATCC CCL-23) were used as host cells for infection by C. pneumoniae J138, isolated in Japan in 1994 (Shirai et al, 2000). C. pneumoniae J138 EBs were purified by sucrose-gradient centrifugation and stored at 280 uC in SPG buffer (pH 7.2), which consists of 250 mM sucrose, 10 mM sodium phosphate and 5 mM glutamate.…”
Section: Introductionmentioning
confidence: 99%
“…RNAIII is also thought to regulate the expression of approximately 110 other genes, but it is not known if this is a direct effect on transcription or the result of post-transcriptional regulation of other transcription factors (Dunman et al, 2001). Recently, Grieshaber et al, 2006 have shown that heterologous expression of a ncRNA from C. trachomatis can block translation of HctA (a chlamydial histone) in E. coli, thereby rescuing chlamydiae from the lethal effects of HctA expression. In addition, they demonstrated that the ncRNA (ihtA) was developmentally expressed in C. trachomatis at times in the cycle when HctA was not expressed.…”
Section: Known Examples Of Ncrnasmentioning
confidence: 99%
“…This lead to the identification of approximately 80 ncRNAs in E. coli between 50 and 400 bases in size (1%-2% of the number of protein-coding genes) (Argaman et al, 2001;Gottesman et al, 2001;Rivas and Eddy, 2001;Wassarman et al, 2001;Kawano et al, 2005). Mechanistically, ncRNAs act through base-pairing interactions with other RNAs, thus inducing premature termination of message (Novick et al, 1989), mediating the destabilization of target mRNAs (Masse et al, 2003;Morita et al, 2005), promoting efficient translation of target mRNA (Majdalani et al, 1998), negatively regulating translation of target mRNA (Grieshaber et al, 2006) by mimicking the structure of other RNAs and DNAs (Willkomm and Hartmann, 2005), or as integral parts of protein-RNA complexes (Ribes et al, 1990) (reviewed in Storz et al, 2004;Gottesman, 2005 andWaters andStorz, 2009). …”
Section: Functional Aspectsmentioning
confidence: 99%